Perbedaan Dukungan Keluarga Tentang Pencegahan Hepatitis B pada Masyarakat Wilayah Desa dan Kota Di Bengkulu - diniarti, Fiya; Zuli, Wahfi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Hepatitis B is a major global health problem. Hepatitis B is a liver infection caused by the hepatitis B virus. The liver is very important for a person's health if the liver is inflamed or damaged, the liver does not function properly and this can affect the health of the human body. The purpose of this study was to determine the differences in family support for the prevention of hepatitis B in communities in rural and urban areas of Bengkulu. This research method uses a quantitative method, this study was conducted in rural and urban areas in Bengkulu in April - May 2024. This study uses a cross-sectional approach with a sampling technique, namely purposive sampling. The sample of this study was the community in the village and city areas in Bengkulu totaling 500 respondents (250 respondents in the village and 250 respondents in the city). This study used data analysis with the Independent Sample T-Test. The results of this study showed that almost all respondents in the village (71.6%) and in the city (80%) were aged 26-45 years. A small portion of respondents' education in the village graduated from high school (32%) and in the city (36%) graduated from high school, a small portion of respondents in the village were not working (27.2%) and a small portion of respondents' jobs in the city as civil servants (41.6%). The results of the Independent Sample T-Test statistical test obtained a p value of 0.008 (P ≤ 0.05), this shows that there is a significant difference between family support for hepatitis B prevention in communities in rural and urban areas. conclusion: the level of family support in urban areas is higher than in villages, both in terms of information, emotional, financial and appreciation/assessment.